Pengembangan Media Pembelajaran Adobe Flash CS6 Pada Materi Kerjasama ASEAN di Sekolah Dasar - Fitria, Anis (Jurnal Penelitian dan Pendidikan IPS, 2025)
This study develops a learning media based on Adobe Flash CS6 for Indonesia’s role in ASEAN cooperation at State Elementary School 1 Wajak. The media is packaged as an Android application for easy operation. The objectives are: (1) to develop learning media based on Adobe Flash CS6 according to the material, (2) to analyze its feasibility, and (3) to analyze its practicality. This research follows a research and development (R&D) approach using qualitative and quantitative data. The development refers to Borg & Gall’s (2003) model with eight stages: research and data collection, initial information, planning, initial product format development, initial trials, product revision, wide field trials, final product revision, and implementation. The results show that the media has a high validity level: content expert (96%, very valid), linguist (94%, very valid), and media expert (80%, valid). The practicality test results show that the teacher’s response was 96% (very practical), student responses in the initial trial were 92% (very practical), and in the wide trial were 93% (very practical). These findings indicate that the developed learning media is feasible, valid, and effective for social science learning.